Annales mvslemici arabice et latine / Abvlfedae ; opera et stvdiis Io. Iacobi Reiskii ; symtibvs atqve avspiciis Petri Fridericci Svhmii ; nvnc primvm edidit Iacobvs Georgivs Christainvs Adler. - Abū al-Fidāʼ Ismāʻīl ibn ʻAlī, 1273-1331. (Tufts University. Tisch Library., 2016)
Volume 3 of 5.; 5 volumes ; 27 cm.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Binding: Tisch Library Special Collections copy: Bound in contemporary tree calf, flat spine tan lettering piece, green numbering piece.